A quality assurance initiative on improving cefazolin perioperative redose compliance. (14th September 2022) - Qureshi, Faiza; Romeiser, Jamie Lee; Murphy, Paul F; Go, Roderick A; Abola, Ramon
Abstract: Objective: Compliance with perioperative antibiotic prophylaxis is crucial for preventing surgical site infection. Anesthesiologists can play a significant role in reducing surgical site infections by following clinical practice guidelines for antibiotic prophylaxis and redosing during surgery. A quality assurance initiative was implemented at a tertiary hospital with the goal of improving cefazolin perioperative antibiotic compliance. Design: This was a retrospective observational study Setting: Main operating room of a tertiary care teaching hospital in New York, USA. Our main operating room includes 22 operating rooms that incorporates surgeries from general surgery, vascular surgery, neurology, gynecology, urology, orthopedics, ear, nose and throat (ENT) etc. Participants: All cases in the main operating room from March 1, 2018 to March 31, 2021 that received first dose of Cefazolin and in which the duration of surgery was more than 4 hrs. Intervention: A multifaceted intervention was initiated to address low compliance with cefazolin redosing. Multifaceted interventions included the development of a perioperative antibiotic guide for anesthesia providers, automated reminders in anesthesia electronic medical records, grand rounds education, survey and email communications, and regular feedback reports to the anesthesia department. Main outcome Measures: Cefazolin perioperative redose compliance rate. Results: Rates of redose compliance were examined in three time periods: preintervention, intervention and postintervention. Cefazolin redosing compliance was 58% in the preintervention period and 90% in the postintervention period. There was a significant positive change in the trend of compliance during the intervention period, indicating that the odds of compliance increased by 13% per month in the intervention period compared to the preintervention period (odds ratio = 1.13, P < 0.001). Redose compliance improvements were sustained a year after the postintervention period (an average of 91%). Surgical site infection rates for colon, coronary artery bypass graft and hip surgeries did not show any significant trend during these time periods. Conclusion: Multifaceted interventions led to significant and sustained improvements in cefazolin redosing compliance in the main operating room of a tertiary hospital.